(untitled) (Acta Scientiarum. Biological Sciences, 2021)
Describing and understanding distribution of species in natural ecosystems is the first step to establish conservation efforts. In aquatic habitats, macrophytes play a central role in promoting biodiversity and ecosystem functioning. This study aimed to create the first checklist of aquatic macrophyte species occurring in the Guaraguaçu river, the largest river in Paraná State coast, Brazil. Species herborized, identified and incorporated into the Herbarium collection of the Universidade Federal do Paraná. A total of 47 species were registered corresponding to 37 genera and 29 botanical families; Cyperaceae and Poaceae were the most representative families. In addition, the wide invasion of the non-native species Urochloa arrecta (Hack. ex T. Durand & Schinz) Morrone & Zuloaga was registered and the presence of the floating-leaved non-native species Nymphaea caerulea Savugny was recorded. Even so, the inventory shows a noteworthy richness of aquatic macrophytes species in the Guaraguaçu river, and it is clear macrophyte species reflect a gradient of anthropic impact and salinity in this tidal estuarine river. Our study contributes to the creation of public policies to aid in the protection of this river that represents a central site for biological conservation efforts, yet is constantly threatened by anthropic activities.